Kurikulum Pai Di Era Digital (Konsep, Desain Dan Implementasinya) - Muhammad Gafarurrozi (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
Abstract: The purpose of this study is to describe the PAI curriculum in the digital era. The development of the digital world today greatly affects activities in carrying out the educational process. These developments have both positive and negative impacts. The curriculum as a determinant of the success of education must be able to answer all the challenges and developments of the times. The curriculum is designed as well as possible so that the goals of education in the digital era can be achieved as expected. This study uses a library research method, in this case the author collects various kinds of literature related to the topic of discussion, namely the Islamic Education curriculum in the digital era. The results of this study are learning in the digital era is very important and good, because learning in the digital era can simplify the teaching and learning process for educators or students and also make it easier to access material by opening journals on the internet. And as long as there is Android and an internet network, this learning can be done anywhere and anytime. Because this digital curriculum is designed to make it easier for educators and students in the teaching and learning process. Because, all activities are in digital form, so they can be done anywhere without space and time limits. Keywords: PAI Curriculum, Digital Era